2023
DOI: 10.11591/ijai.v12.i3.pp1508-1520
|View full text |Cite
|
Sign up to set email alerts
|

Discrete separation of patients’ profiles for chronical obstructive pulmonary disease context-aware healthcare efficient systems

Abstract: According to the Public Health Agency of Canada (PHAC), the symptoms of chronic obstructive pulmonary disease (COPD) are shortness of breath, coughing, and sputum production. Many studies estimate that COPD will become the third-leading cause of death worldwide by 2030 (WHO,2008). Pervasive healthcare systems cover healthcare issues, including chronic diseases; they help patients to manage their own health information and healthcare services at any time and in any place. We developed a COPD healthcare system b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The World Health Organization (WHO) found that IoT can help save lives by facilitating early disease identification and management, as well as increasing access to care and decreasing medical errors. Rapid expansion and increased importance in terms of both income and employment have been characteristics of the healthcare sector in recent years [4]. Just a few short years ago, medical professionals needed to perform a thorough physical examination of a patient to diagnose illness or abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) found that IoT can help save lives by facilitating early disease identification and management, as well as increasing access to care and decreasing medical errors. Rapid expansion and increased importance in terms of both income and employment have been characteristics of the healthcare sector in recent years [4]. Just a few short years ago, medical professionals needed to perform a thorough physical examination of a patient to diagnose illness or abnormalities.…”
Section: Introductionmentioning
confidence: 99%